Stellenwert und qualitative Voraussetzungen der Magnetresonanztomografie für die Therapieplanung beim lokal fortgeschrittenen Rektumkarzinom - Interdisziplinäre Empfehlungen - Attenberger, Ulrike; Rödel, Claus; Ghadimi, Michael; Piso, Pompilio; Arnold, Dirk; Folprecht, Gunnar; Geißler, Michael; Hegewisch-Becker, Susanna; Heinemann, Volker; Kasper-Virchow, Stefan; Modest, Dominik Paul; Reinacher-Schick, Anke Claudia; et al. (Zeitschrift für Gastroenterologie, 2020)
For the purpose of indication and patient stratification of perioperative treatment of locally advanced rectal cancer, magnetic resonance imaging (MRI) has become indispensable. In this report, we describe the importance of MRI diagnostics and the qualitative conditions.